Experimental assessment of the effectiveness of electromagnetic therapy in purulent and burn wound healing process - Vishrabdha Chandrakant Margaj et al (Global Wound Care Journal, 2026)
Introduction: Wound infection is a significant healthcare problem, and electromagnetic therapy (EMT) is a promising tool to reduce bacterial load and promote wound healing. Aim: This study aimed to provide an objective assessment of efficacy of EMT in healing of purulent and burn wounds in experimental animals. Methods: Our prospective, non-randomised study enrolled 28 non-pedigree rabbits aged 2-3 months, divided into two groups. Wounds of the experimental group (n=14) were treated with local EMT using a TOR electromagnetic therapy device. The control group (n=14) was treated with 0.9% physiological saline solution. After 14 days of treatment, the wounds were assessed daily using planimetry and a bacteriological culture test. SPSS 17.0 was used to analyse the data. Results: After 5 days of treatment, the experimental group was found to have a statistically significantly higher healing rate (p